Slotted ALOHA CDMA By Dual Model Path Gains - Hoga Saragih; Djoko Soetarno (CCIT Journal, 2009)
Throughput Slotted ALOHA CDMA by dual model path gain Nakagami/Nakagami fading channel by capture effect is analyzed. The approach of fading effect to BER is calculated by path gain. Path gain for desired signal and interference signal is unequal. Therefore, at this research BER used on S-ALOHA CDMA is BER with two different model path gains at Nakagami/Nakagami fading channel with capture effect. Result of calculation indicates that throughput of slotted ALOHA CDMA are getting better with increase level of parameter fading signal and long code. Others throughput slotted ALOHA CDMA also better progressively with the decrease of capture ratio and simultaneous user.